(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article analyzes the main approaches to the use of sports games in the school physical education system. The most important purpose of sports in secondary school is to acquaint students with the types of sports games and exercises, to lay the foundation for the right technique.